Gm allotypes and HLA in rheumatoid arthritis patients with circulating antibodies to native type II collagen. Issue 5 (May 1987) - Sanders, P A; Grennan, D M; Klimiuk, P S; Clague, R B; deLange, G G; Collins, I; Dyer, P A
Abstract : HLA antigens and immunoglobulin heavy chain allotypes (Gm) were determined in 166 unrelated patients with rheumatoid arthritis (RA), 44 of whom had circulating antibodies to native type II collagen. Collagen antibody positive patients showed an association with HLA-DR3 and DR7 (68% compared with 39% of collagen antibody negative RA, p less than 0.005), and with the Gm phenotype, Gm(zafngb). This contrasted with the collagen antibody negative RA patients where there was an association with HLA-DR4 and, in DR4 positive disease only, with the Gm allotype, G1m(x). The Gm(zafngb) phenotype was found in 26% of DR3 or DR7 positive patients overall and only 9% of RA patients negative for these DR antigens (p less than 0.005), suggesting an interaction between HLA-DR3/7 and Gm(zafngb). The differing Gm associations for collagen antibody positive and negative RA provide further evidence for genetic heterogeneity in susceptibility to RA.